How Patients' Self‐Disclosure about Sickle Cell Pain Episodes to Significant Others Relates to Living with Sickle Cell Disease. Issue 9 (26th August 2014) - Derlega, Valerian J.; Janda, Louis H.; Miranda, Jeannie; Chen, Ian A.; Goodman, B. Mitchell; Smith, Wally
Abstract Objectives This cross‐sectional study examines to whom and how fully sickle cell disease (SCD) patients talk to others about sickle cell pain, how helpful it is to talk with others about these pain episodes, and the association between talking to others about sickle cell pain episodes and patients' psychological adjustment and coping strategies in managing the disease. Methods A convenience sample of 73 African American patients with SCD (30 men and 43 women), were recruited from two SCD clinics at the time of routine medical visits. Most participants had been diagnosed with hemoglobin SS, and they reported an average number of 8.61 pain episodes in the previous 12 months. Participants were asked to whom, how fully, and how helpful it was to talk to significant others about SCD pain episodes experienced in the last 12 months. Patients also completed measures of their psychological adjustment as well as how they would manage a future sickle cell pain episode. Self‐report ratings were made on Likert‐type scales. Results Based on paired samples t‐tests, participants talked significantly more fully about their thoughts and feelings concerning pain episodes to God and to their primary medical providers than to either their parents, siblings, or an intimate partner/close friend. Bivariate correlations indicated that amount and helpfulness of talking about pain episodes to God and to parents were significantly associated with better psychological adjustment on selected measures. Also, bivariate correlations indicated that helpfulness in talking with siblings, intimate partner/close friend, and primary medical providers was positively related with willingness to go to a physician in the event of a future pain episode. Conclusions The results document to whom and how helpful it is to talk with others about SCD pain episodes and how SCD disclosure is related to strategies for managing this disease.